2013
DOI: 10.1139/cjpp-2012-0419
|View full text |Cite
|
Sign up to set email alerts
|

Altered calcium regulation in isolated cardiomyocytes from Egr-1 knock-out mice

Abstract: Early growth response-1 one gene (Egr-1), one of the immediate early response genes, plays an important role in the adaptive response of the myocardium to hypertrophic stimuli. We aimed to investigate the effects of Egr-1 deletion on cardiac function. Egr-1 knock-out (Egr-1(-/-)) homozygous mice were employed to evaluate the electrophysiological and molecular properties of left ventricular cardiomyocytes (VCM) by using patch-clamp technique, intracellular calcium measurements, real-time PCR, and Western blot. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…[41][42][43]65,66 In addition, our gene expression studies showed upregulation of 2 members of the early growth response gene (Egr) family, in particular Egr1 (4.25-fold) in the KO muscle; Egr1 is a physiological regulator of genes involved in calcium handling including L-type Ca 2C channel. 67 We reasoned that the increased CACNB1 in Pompe muscle cells triggers the observed surge in cytosolic Ca 2C levels and mitochondrial Ca 2C overload-a condition which is exacerbated with age of the animal and is not resolved by treatment with the therapeutic enzyme. An increase in Ca 2C levels in Pompe cells could lead to the increased autophagy, but this relationship is a subject of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…[41][42][43]65,66 In addition, our gene expression studies showed upregulation of 2 members of the early growth response gene (Egr) family, in particular Egr1 (4.25-fold) in the KO muscle; Egr1 is a physiological regulator of genes involved in calcium handling including L-type Ca 2C channel. 67 We reasoned that the increased CACNB1 in Pompe muscle cells triggers the observed surge in cytosolic Ca 2C levels and mitochondrial Ca 2C overload-a condition which is exacerbated with age of the animal and is not resolved by treatment with the therapeutic enzyme. An increase in Ca 2C levels in Pompe cells could lead to the increased autophagy, but this relationship is a subject of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…Adult rat left ventricular myocytes (ARVM) were obtained from 3-month-old rats (Pacini et al, 2013;Ferrantini et al, 2014). Animal studies were performed according to the University of Florence laboratory animal guidelines.…”
Section: Rat Cardiomyocyte Isolation and Culturementioning
confidence: 99%
“…Furthermore, Egr-1 deficiency is very sensitive to the perturbation of intracellular calcium homeostasis, because only treatment of Egr-1 knockdown cells with thapsigargin, which inhibits SERCA leading to calcium depletion in ER, causes further increases in ER stress and cell death. Altered calcium regulation has been found in Egr1 −/− cardiomyocytes through downregulation of major proteins involved in control of calcium homeostasis [35,36]. Thus, we speculate that attenuation of ER stress by Egr-1 in β-cells may mediate through remodeling of calcium homeostasis.…”
Section: Discussionmentioning
confidence: 95%